2020
DOI: 10.1186/s12951-020-00659-6
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, translocation and biotransformation of selenium nanoparticles in rice seedlings (Oryza sativa L.)

Abstract: Background: Selenium (Se) in soil mainly consists of selenite, selenate, and elemental Se. However, little is known about the mechanism involved in the uptake and biotransformation of elemental Se by plants. Results: In this study, the uptake, translocation, subcellular distribution and biotransformation of selenium nanoparticles (SeNPs) in rice (Oryza sativa L.), and a comparison with selenite and selenate, were investigated through hydroponic experiments. The study revealed that SeNPs could be absorbed by ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…SeNPs pass through a cell wall and penetrate the plasma membrane. Only NPs aggregates with diameters smaller than pore diameter could pass through the cell wall successfully [41]. The cell wall of the plant acts as a barrier, preventing easy entry of any external influences, including SeNPs, into the plant's cell walls.…”
Section: Uptake Of Senps By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…SeNPs pass through a cell wall and penetrate the plasma membrane. Only NPs aggregates with diameters smaller than pore diameter could pass through the cell wall successfully [41]. The cell wall of the plant acts as a barrier, preventing easy entry of any external influences, including SeNPs, into the plant's cell walls.…”
Section: Uptake Of Senps By Plantsmentioning
confidence: 99%
“…These sieving properties are determined by the pore size of the cell wall, which can range from 5 to 20 nm [42]. It was shown that SeNPs could abide by plant roots and could influence a chemical and physical uptake in plants [41]. The most widely accepted explanation for the translocation of engineered nanomaterials is that such nanomaterials can start moving intracellularly and extracellularly among the plant tissues until they reach the xylem [43].…”
Section: Uptake Of Senps By Plantsmentioning
confidence: 99%
“…Additionally, Se speciation in leaves was distinguished by high-performance liquid chromatography coupled to hydride generation atomic uorescence spectrometry (HPLC-AFS; SA-20, Beijing Jitian Instruments, Beijing, China) with three biological replicates (Wang et al 2020). Brie y, 0.8 g of fresh leaves of SeUn or Un was hydrolyzed by 5 mL of 8 mg mL − 1 protease XIV (Sigma-Aldrich, St. Louis, MO, USA) at 37℃ for 12 hours.…”
Section: Se Transformation and Speciation In Pretreated Leavesmentioning
confidence: 99%
“…Previous studies have identified the potential of SeNPs to promote plant growth, increase Se uptake and improve plant quality (Domokos-Szabolcsy et al, 2012;Hussein et al, 2019). The beneficial effects of SeNPs have been shown for several plants, including tomato (Hernandez-Hernandez et al, 2019;Morales-Espinoza et al, 2019), pomegranate (Zahedi et al, 2019), wheat (Hu et al, 2018), rice (Wang et al, 2020a), garlic (Li et al, 2020) and tobacco (Domokos-Szabolcsy et al, 2012). Besides, SeNPs have lower toxicity for plants compared to selenite and selenate (El-Ramady et al, 2020;Li et al, 2020).…”
Section: Nano-se For Biofortificationmentioning
confidence: 99%
“…Besides, SeNPs have lower toxicity for plants compared to selenite and selenate (El-Ramady et al, 2020;Li et al, 2020). SeNPs taken up by plants were quickly oxidized to selenite and transformed to organic Se species (e.g., SeCys, SeMet and MeSeCys) in the plant root (Hu et al, 2018;Wang et al, 2020a). However, further investigations are still required to understand the phytotoxicity of SeNPs on various plants and the potential risks to the environment of using SeNPs.…”
Section: Nano-se For Biofortificationmentioning
confidence: 99%